Towards computational design of zeolite catalysts for CO2 reduction1. Issue 55 (17th June 2015) - Thornton, A. W.; Winkler, D. A.; Liu, M. S.; Haranczyk, M.; Kennedy, D. F.
<x xml:space="preserve">Abstract</x> Computational search of structure database for CO2 reduction catalysts using molecular simulation and machine learning.